Revitalizing the School Library’s Role in Increasing Reading Interest among Elementary Students: A Case from Ombolata Alasa - Hulu, Lena Febrianis (CV Media Inti Teknologi, 2025)
Background: Libraries in schools are essential facilities that contribute significantly to the development of students’ literacy skills. They function as learning centers that encourage reading habits and enhance the overall learning process. However, many schools still lack well-equipped libraries with proper management. SD Negeri 071150 Ombolata Alasa, located in a remote area, faces multiple challenges in managing its library, yet continues to strive to optimize its role in supporting students’ literacy activities.Aims: This study aims to explore and identify the role of the school library in improving students’ reading interest at SD Negeri 071150 Ombolata Alasa, and to evaluate the literacy programs implemented to achieve this objective.Method: The study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with principals, librarians, teachers, and students; direct observations of library activities; and document analysis related to the school’s literacy programs.Results: Findings show that despite the limited book collection, the school library still plays a significant role in enhancing students’ reading interest. Literacy activities such as reading competitions, group reading sessions, and storytelling have successfully increased students’ motivation to visit the library and read more books. The library remains a key driver in fostering reading habits despite the need for improved facilities and resources.Conclusions: The study concludes that with creativity and effective library management, even schools with limited resources can maximize the role of libraries in encouraging students’ reading interest. Enhancing library collections and facilities would further strengthen the impact of existing literacy initiatives.